Lexical Cohesion in Escape Room Movie Script: Discourse Analysis - Dhani Lesmana; Heri Heriyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the important elements in a sentence is lexical cohesion. This study aims to describe the lexical cohesion used in the escape room film script. The method used is to take quantitative data in the movie script Escape Room. Data analysis was carried out by identifying and classifying data related to cohesion, based on the theory of Halliday and Hasan (1976). Based on the analysis, in this study, the most dominant types of lexical cohesion and lexical cohesion in the Escape Room film script were analyzed. There are six types of lexical cohesion found in the Escape Room movie script consisting of repetition, synonyms, antonyms, hyponym, meronyms and collocations. This study used 30 samples of data obtained in the escape room film script which included lexical cohesion, repetition (60%), synonyms (10%), antonyms (10%) hyponyms (5%), meronyms (5%) and collocations (10%). The most dominant lexical cohesion and often appears in the escape room movie script is repetition.